Pengaruh Profitabilitas, Likuiditas, dan Solvabilitas terhadap Return Saham pada Sub Sektor Otomotif Tahun 2020-2022 - Makhsunnah, Cindy Eka; Susilo, Dwi Ermayanti (Al-Kharaj : Jurnal Ekonomi, Keuangan & Bisnis Syariah, 2024)
This research uses a quantitative research approach and aims to empirically prove the influence of profitability, liquidity and solvency on stock returns in automotive sub-sector companies listed on the Indonesia Stock Exchange. Share returns are rewards given by the company to investors for investing their funds in a company. In taking samples using purpose sampling techniques with predetermined criteria, 11 companies were obtained over 3 years so that the total sample obtained was 33 data. This research uses a multiple linear regression analysis method using multiple linear analysis tools. Profitability is proxied by Return on Assets (ROA), Liquidity is proxied by Current Ratio, and Solvency is proxied by Debt to Equity Ratio (DER). The research results prove that Profitability (ROA) has a positive effect on Stock Returns in automotive sub-sector companies listed on the Indonesia Stock Exchange, so the first hypothesis is accepted. Liquidity (Current Ratio) does not have a positive influence on stock returns. Solvency (DER) has a positive influence on stock returns. Keywords: Profitability; Liquidity; Solvency; Stock Return